Rekonstruksi Peran Pemerintah Dalam Memberikan Perlindungan Hukum Bagi Pengemudi Transportasi Online - Tri Rahayu Utami; Naila Amrina; Adilla Cindy Jonfita; Muhamad Azhar (Administrative Law Department, Faculty of Law, Universitas Diponegoro, 2020)
Abstract The presence of online transportation services provides benefits in terms of easy and fast mobilization. This scientific article aims to determine the pattern of partnerships between online transportation drivers and companies and the government's opportunities to provide more protection for online transportation drivers. The narrative review method is used by examining various scientific literature that specifically discusses online transportation. The data extraction procedure is carried out by deepening the idea, methodology, and reviewing the scientific literature. The results showed that the practice of the partnership relationship between online transportation drivers and companies was not in accordance with the principles of partnership and protection practices for online transportation drivers through bestuurshandeling instruments that were not optimal.Key words: Administrative act, Protection, Online Transportation.AbstrakKehadiran jasa transportasi online memberikan manfaat dalam hal mobilisasi yang mudah dan cepat. Artikel ilmiah ini bertujuan untuk mengetahui pola hubungan kemitraan antara pengemudi transportasi online dengan perusahaan dan peluang pemerintah untuk lebih memberikan perlindungan bagi pengemudi transportasi online. Metode narrative review digunakan dengan menelaah berbagai literatur ilmiah yang khusus membahas transportasi online. Prosedur ekstrasi data dilakukan dengan melakukan pendalaman terhadap ide, metodologi, dan telaah literatur ilmiah. Hasil penelitian menunjukkan bahwa praktik pola hubungan kemitraan antara pengemudi transportasi online dan perusahaan tidak sesuai dengan prinsip kemitraan dan praktik perlindungan bagi pengemudi transportasi online melalui instrumen bestuurshandeling yang belum maksimal. Kata kunci: Bestuurshandeling, Perlindungan, Transportasi Online.